Enhancement and Optimization of the Mechanical Properties in Cement Concrete with Recycled Asphalt Pavement (RAP) - Ahmed H. Alwathaf; Mu’tasim Abdel Jaber; Yasser M. Hunaiti (Buildings)
Using recycled asphalt pavement (RAP) as a natural aggregate (NA) replacement supports environmental preservation but requires performance evaluation. This study investigated the mechanical properties of concrete containing RAP and the potential of silica fume (SF) and superplasticizer (SP) to enhance these properties. Thirty-five concrete mixtures were prepared with a 0%, 25%, 50%, 75%, or 100% replacement of natural coarse aggregate by crushed coarse RAP. SF (0–21%) and SP (0–2.1% per 100 kg of cement) were added separately as admixtures. Tests on compressive, splitting, and flexural strength showed that RAP generally reduced compressive and splitting tensile strength but increased flexural strength at low RAP content. SF and SP partially restored strength losses, with higher RAP content benefiting more from these admixtures. Optimal compressive strength gains ranged from 8% to 58%, with splitting and flexural tensile strength improvements of 40% and 28%, respectively. The ideal SF and SP contents were 5–7% and 0.8–1.5%, respectively. These findings demonstrate that 100% RAP concrete, combined with appropriate admixtures, can meet performance requirements, offering a sustainable solution for structural applications and promoting resource conservation.